Progress in functional manufacturing technologies III - Taiyong, Wang (Key engineering materials, 2014)
The special volume communicates the latest progress and research results of new theory, new technology, method, equipment and so on in advanced manufacturing technology field, and to grasp the updated technological and research trends internationally. The major topics covered by the special volumes include Applied Materials Engineering, Materials Processing Technologies and Mechanical Engineering, Monitoring Method and Technology in Mechanical Engineering, Control System in Mechanical Engineering, Management and Development of Manufacturing Technologies. In invited and peer reviewed reports, r.